Full Mouth Oral Rehabilitation by Maxillary Implant Supported Hybrid Denture Employing a Fiber Reinforced Material Instead of Conventional PMMA - Ala Hassan A. Qamheya; Sinem Yeniyol; Volkan Arısan (Case Reports in Dentistry)
Many people have life-long problems with their dentures, such as difficulties with speaking and eating, loose denture, and sore mouth syndrome. The evolution of dental implant supported prosthesis gives these patients normal healthy life for their functional and esthetic advantages. This case report presents the fabrication of maxillary implant supported hybrid prosthesis by using Nanofilled Composite (NFC) material in teeth construction to rehabilitate a complete denture wearer patient.